New marine reptile assemblage from the Jurassic-Cretaceous boundary beds of the High Andes, Argentina - Fernández, Marta S. (2018)
Fil: Fernández, Marta S. Universidad Nacional de La Plata. Museo de La Plata. División Paleontología de Vertebrados. Buenos Aires, Argentina.